The formation of flavoring characteristics of meat products by changing the chemical composition of food compositions - A. N. Ivankin; N. L. Vostrikova; O. N. Krasulya; E. V. Kazakova; A. V. Kulikovskii; A. S. Knyazeva (Теория и практика переработки мяса)
The article presents the results of the study of changes in flavour characteristics when using corrective additives. Monosodium glutamate, ribotide, yeast extract and hydrolysate of vegetable soy protein were used as flavoring additives (FA). To assess the effect of composition of meat product recipe, as well as the method of FA‑introduction on taste intensity, the recipes of model meat systems with partial replacement of meat raw materials were used. Pork fat, soy protein and potato starch were used as meat substitutes. The effect of recipe composition on the content of non-volatile substances of aroma was accessed. It is shown that replacement of pork by pork fat in the recipe by 20–40% led to a sharp decrease in the concentration of aromatic substances and a decrease in intensity of taste of the finished product several times. The ways for taste correction using FA was studied. For this, a chopped semi-finished product — minced meat was prepared from chilled whole-muscle pork and 0.05% of each FA was added. It is shown that the dynamics of changes in the content of free amino acids is the most pronounced when using monosodium glutamate not as a mono-additive, but in compositions: monosodium glutamate with yeast extract and monosodium glutamate with ribotide. A pool of chemical compounds involved in the formation of taste and aroma of products was detected. The main components were derivatives of C6–C24 fatty acids, as well as a significant number of other biochemical compounds, mainly substituted amines, amides, alcohols and ketones, with a content ranging from 0.001 to 0.2 mg/kg. The results of organoleptic analysis showed that the most delicious and attractive samples were those containing monosodium glutamate with yeast extract and monosodium glutamate with ribotide.